Labels de la construction : quelle contribution possible au facteur 4 ? - Jonathan Villot; Natacha Gondran; Valérie Laforest (Développement Durable et Territoires)
Factor 4, which is often presented as an objective to deal with energy and climate change issues, is characterized by a double identity. Referring at the same time to an increase of resources productivity (factor 4 for energy) and to greenhouse gas attenuation (factor 4 for climate), it constitutes challenge to be reached in 40 years. To this end, the various branches of industry have adapted these concepts. In the building sector, this appropriation has been translated since 1990 by the creation of labeling systems. The labels by their standardized approach endeavor to be the precursors and the essential to drive these changes to the factors 4. The goal of this paper is to study the various types of labels that apply to sustainable construction and to study how and at which degree they contribute to factors 4 objectives.